Identification of Larvicide-Resistant Catch Basins from Three Years of Larvicide Trials in a Suburb of Chicago, IL - Justin E. Harbison; James M. Sinacore; Marlon Henry; Christopher Xamplas; Lara R. Dugas; Marilyn O'Hara Ruiz (SAGE Publishing, 2014)
The tens of thousands of catch basins found in many urban areas are a primary target of local vector control agencies for seasonal application of extended-release larvicides. A concern with using larvicides in these structures is that active ingredients can be hampered by high flows, debris, and sediment, all of which are common to these structures. As such a certain proportion of basins may be "resistant" to larvicide treatments due to site specific characteristics that may promote these and other factors that hinder larvicide action and/or promote mosquito infestation. Analyses from three years of larvicide efficacy trials suggest that over a quarter of basins in the study area may not be receiving adequate protection from a single dose of larvicide that is routinely applied. Implications of increasing the dose and/or toxicity of larvicide treatments are discussed further.